Formation of a New Organizational and Economic Mechanism Enhancing the Functional Role of Population's Savings in Financing Investments - TATUEV, Arsen A.; KUTSURI, Georgiy N.; SHANIN, Sergey A.; ROKOTYANSKAYA, Violetta V.; OVCHAROVA, Nataliya I. (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The article examines the problem of economic development within a context of reductions of the investment resources. Russian economy is characterized by one of the highest borrowing costs. This affects the development of the real economy, as investment demand is shifting towards highly profitable projects. But the investments in the real sector have naturally lower profitability than financial speculations in securities of operating companies. In such circumstances, it is advisable to form a new organizational and economic mechanism of financing economic growth and modernization. The savings of the population should play a key role in this system, being the most important source of domestic investment.